1984
DOI: 10.1111/j.1348-0421.1984.tb02943.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonial Morphology of Treponemes Observed by Electron Microscopy

Abstract: The colonial morphology of three strains of cultivable, nonpathogenic treponemes including a human oral treponeme was examined by light and electron microscopy. Treponema phagedenis strains Kazan and Reiter produced large white colonies on the surface of solid media composed of sterility test broth, 0.9 to 3.1% agar, rifampin, and 12.5% rabbit or horse serum. A human oral treponeme, strain G7201, grew as diffused white zones on 0.9 to 3.1% agar plates. Under the cultural conditions employed agar concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Likewise, members of the phylum Spirochaetae are not exempt from this trait, and notable examples include Treponema spp. [311,312], and Borrelia spp. [270,[313][314][315].…”
Section: Pleomorphymentioning
confidence: 99%
“…Likewise, members of the phylum Spirochaetae are not exempt from this trait, and notable examples include Treponema spp. [311,312], and Borrelia spp. [270,[313][314][315].…”
Section: Pleomorphymentioning
confidence: 99%
“…Agar plugs at the leading edgc of the haze were cut with a sterile glass pipette and were transferred into agar wells in fresh agar plates. In order to obtain a pure culture, the procedure was repeated more than 10 times, and spirochetal colonies were picked from solid sterility test medium supplemented with horse serum (35). Later, TYGVS medium was used as the routine culture medium and an anaerobic chamber (85% N,, 10% H,, 5% COz) was used for anaerobic conditions (34,36).…”
Section: Methodsmentioning
confidence: 99%
“…A host-associated treponeme, strain G7201, was isolated from the subgingival plaque of a 52-year-old man with adult periodontitis by a well-plate method (16,24,25). It has been shown that the organism was moiphologically and serologically different from any of the previously established oral Treponema species by the studies using scanning electron microscopy (24,25). Currently, DNA-DNA reassociation or 16S rRNA sequence analysis is recommended to determine whether a microorganism is a new species.…”
mentioning
confidence: 99%